Peasants, the State and Aid: Rural Development and Poverty in Cape Verde - Carlos Ferreira Couto (Modern Africa, 2014)
Based on employment-intensive public works, international food aid implemented a model in several countries with varying rates of success. Through the sale of foodstuffs, food aid in Cape Verde originated a “monetized” help system called “cash-for-work”. This system consisted of recruiting workers from rural areas for the construction of infrastructure projects for the conservation of soil and water. Also the construction of roads creates income for rural families, during their free time from the traditional activities such as composting, sowing and harvesting of dry land agriculture. The result was the establishment of a food aid program in Cape Verde through the 1980s and 1990s that represents a combination of several types of programs. These programs intend to guarantee long-term employment as well as the creation of an infrastructure. Therefore it was not a program of emergency food aid. Santiago`s rural production relationship develops alongside the transformation in social structures based on the traditional forms of cooperation of work and mutual assistance. This is in response to developmental actions through the rural development projects. These transformations in the peasants’ social organization refer to the importance of reciprocity in peasant society. In the Santiago case, this possibility is settled by using a device to reduce uncertainty, a kind of shape memory behavior, where collective reciprocity of the social structure, built on peasant institutions, was to maintain a negative relationship with modernizing external interventions. Development/underdevelopment, is the result of the action of economic agents in a precise contexts. The decision of rural economic agents as minimum resource managers is the essential ingredient to the "modernization" of peasant self-management, fostering the co-evolutionary process (progression) of different elements of social design.